Evaluating Microbial Quality of Drinking Water from Wells and Boreholes in Michika LGA and Its Impact on Community Health - Umaru, Isaac John; Asare, Solomon Ossom; Olayeni, Abimbola Gbenga; Johnson, Joanna Afariba; Amofa, Gift (African Journal of Sciences and Traditional Medicine, 2025)
Access to safe drinking water remains a critical public health challenge in rural Nigeria, particularly in Michika Local Government Area (LGA) of Adamawa State, where communities depend on wells and boreholes for their daily water needs. This study evaluates the microbial quality of these groundwater sources and examines their impact on community health. Microbiological analyses revealed widespread contamination, with elevated levels of Escherichia coli, total and fecal coliforms, and high turbidity, especially in wells located in districts such as Zah, Moda, and Minkisi. Physicochemical parameters, including acidic pH and elevated temperatures, further exacerbated microbial proliferation. Environmental assessments identified key contamination sources—proximity to latrines and refuse dumps, open well structures, poor drainage, and unrestricted animal activity—which correlated strongly with high incidences of waterborne diseases, notably diarrhea, typhoid, and cholera, predominantly affecting children under five, pregnant women, and the elderly. In contrast, boreholes in Diaka and Michika Town demonstrated safer profiles due to better infrastructure and maintenance. The findings underscore the urgent need for integrated water, sanitation, and hygiene (WASH) interventions, routine water quality monitoring, and community education to mitigate health risks and promote sustainable access to potable water in Michika LGA.